A Study Of Psychophysical Factor (Heart Rate) For Driver Fatigue Using Regression Model - Kamat, Seri Rahayu; Ani, Mohammad Firdaus; M, Mohamad; Hambali, Ruzy Haryati; Husain, Kalthom (Malaysian Public Health Physicians' Association, 2018)
Driving activity has become more important as this medium being practical,it is also cheaper and faster in connecting human from one to another place.However,in some occurrence,it can cause accidents as they become fatigued while driving.Driver fatigue is one of the top contributors to the road accidents and can be dangerous as other road safety issues such as drink driving.Worst is,there are no laws regulating driver fatigue.Therefore, the main purpose of this study is to develop the regression model of apsychophysical factor for drivers’ fatigue which can predict the relationship between the process input parameters and output responses.The study was participated by ten subjects.The heart rate was taken and recorded using heart rate monitor.Design Expert 8.0.6 software was used for the regression analysis.The modeling validation runs werewithin the 90% prediction intervals of the developed model and the residual errors were less than 10%.The R2 value is 0.9400 whichmeans that the linear regression line passed exactly through all points.The significant parameters that influenced the heart rate were also identified.The parameters are time exposure,type of road,and gender.